Exogenous Application of Ascorbic Acid Enhances the Antimicrobial and Antioxidant Potential of Ocimum sanctum L. Grown under Salt Stress - Neelma Munir; Sheza A. Khilji; Maryam Shabir; Zahoor A. Sajid (Journal of Food Quality)
Ocimum sanctum L. (Tulsi) is the most important medicinal plant that has antimicrobial, antioxidants, and anticarcinogenic effects on human health. Plants, when under stress, gather several antioxidants and osmoprotectants. The present work focuses on the abiotic stress response of Tulsi and its mitigation by the application of ascorbic acid. In addition to this, an enhancement of antioxidant and antimicrobial activity was also analyzed using ascorbic acid. During the present work, when plants were grown under NaCl stress and ascorbic acid (AA) was provided with foliar applications, it ascertained encouraging effects on growth; likewise, its effect remains stable under salinity stress. The enzymatic antioxidants activity showed a significant change in response to AA alone or in combination. The highest catalase activity was recorded in plants subjected to 0.5 mM AA in combination with 100 mM NaCl (0.65 units/mL of enzyme). Likewise, a similar trend was recorded for the superoxide dismutase activity of Tulsi plants. The highest activity of SOD was recorded in plants subjected to 0.5 mM AA in combination with 100 mM NaCl (66.1 units/mg of protein). Flavonoid content showed its highest amount (27.41 mg/g) when plants were treated with 0.5 mM AA + 100 mM NaCl while the highest phenolic content (1.88 mg/g) was analyzed in salt treated plants sprayed with 0.5 mM AA. In the case of antimicrobial activity, 0.5 mM AA treated plants gave the highest value for the Staphylococcus aureus as 2.15 cm and in Clostridium species was 2.1 cm in the plants treated with 1 mM AA alone. Hence, the findings of the present study may lead to the conclusion that AA has a significant role in defense mechanisms of plants in response to salt stress. Further, it enhances the antimicrobial and antioxidant potential of Tulsi plants grown under salt stress.